2019
DOI: 10.1021/acsami.9b15815
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Separation of Aromatic Sulfide from Liquid Hydrocarbon Fuel in Conjugated Porous Organic Framework with Polycarbazole Unit

Abstract: We synthesized three conjugated polycarbazole porous organic frameworks named o-Cz-POF, m-Cz-POF, and p-Cz-POF for hydrocarbon fuels’ adsorptive desulfurization. The carbazole building blocks possessed ortho, meta, and para steric configuration, which resulted in POFs exhibiting adjustable specific surface area and pore structure. Adsorption kinetics experiments and DFT calculations were carried out to understand the competitive adsorption of 3-methylthiophene and octane in the Cz-POF. The instantaneous adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Three conjugated polycarbazole porous organic frameworks, named o-Cz-POF, m-Cz-POF, and p-Cz-POF, that possessed ortho, meta, and para steric configuration, were also examined for adsorption of 3methylthiophene [85]. The highest uptake amount of 3-methylthiophene was observed in m-Cz-POF, which could reach 7.762 mmol/g (248.4 mg of S/g) at 298 K. This value is far beyond those of the porous absorbents previously reported [85]. Various MOFs have been used to selectively adsorb organo-sulfur compounds [59,86].…”
Section: Desulfurization With Mofsmentioning
confidence: 99%
“…Three conjugated polycarbazole porous organic frameworks, named o-Cz-POF, m-Cz-POF, and p-Cz-POF, that possessed ortho, meta, and para steric configuration, were also examined for adsorption of 3methylthiophene [85]. The highest uptake amount of 3-methylthiophene was observed in m-Cz-POF, which could reach 7.762 mmol/g (248.4 mg of S/g) at 298 K. This value is far beyond those of the porous absorbents previously reported [85]. Various MOFs have been used to selectively adsorb organo-sulfur compounds [59,86].…”
Section: Desulfurization With Mofsmentioning
confidence: 99%
“…Porous aromatic frameworks (PAFs) are an emerging material with a rigid framework and C–C bond linkage . Since the synthesis of the first diamondoid PAF-1, these materials have led to great breakthrough in applications such as catalysis and gas capture owing to their high specific surface area and chemical stability. Furthermore, the rigid aromatic components of PAFs make it possible to introduce functional groups into their backbone without framework decomposition and also allow the PAFs to retain their structural integrity under harsh conditions, which greatly expand the application of porous frameworks. Specifically, PAFs are entirely composited by organic compounds without any metal in the framework. Compared with metal organic frameworks of which the metals are incorporated in the frameworks through relatively weak coordinating bonds, there is no concern on metal leaking and exchange occurs when PAFs are used for metal capture.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al also found this phenomenon in which the N 2 sorption capacity increased sharply at a relatively lower pressure (p/p 0 < 0.1) and attributed it to the presence of micropores. 49 Furthermore, the change of pore size and distribution for CMS membranes was also studied with increasing heattreatment temperature presented in Figure 6b using N 2 adsorption. The co-polyimide precursor was a non-porous dense membrane.…”
Section: Structure Evolution Of Membranes During Pyrolysismentioning
confidence: 99%